2012
DOI: 10.1186/1476-072x-11-13
|View full text |Cite
|
Sign up to set email alerts
|

Near-present and future distribution of Anopheles albimanus in Mesoamerica and the Caribbean Basin modeled with climate and topographic data

Abstract: BackgroundAnopheles albimanus is among the most important vectors of human malaria in Mesoamerica and the Caribbean Basin (M-C). Here, we use topographic data and 1950–2000 climate (near present), and future climate (2080) layers obtained from general circulation models (GCMs) to project the probability of the species’ presence, p(s), using the species distribution model MaxEnt.ResultsThe projected near-present distribution parameterized with 314 presence points related well to the known geographic distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 23 publications
3
55
0
1
Order By: Relevance
“…Although it is one of the more recently developed methods compared to other traditional models, such as generalised linear models or generalised additive models, the MaxEnt model has been among the most efficient method for predicting species distribution (Elith et al, ; Fuller, Ahumada, Quinones, Herrera, & Beier, ; Reiss, Cunze, König, Neumann, & Kröncke, ). MaxEnt is also one of the most commonly used methods for projecting shifts in species distribution under various climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is one of the more recently developed methods compared to other traditional models, such as generalised linear models or generalised additive models, the MaxEnt model has been among the most efficient method for predicting species distribution (Elith et al, ; Fuller, Ahumada, Quinones, Herrera, & Beier, ; Reiss, Cunze, König, Neumann, & Kröncke, ). MaxEnt is also one of the most commonly used methods for projecting shifts in species distribution under various climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Among Latin American malaria vector mosquitoes, Anopheles albimanus Wiedemann, 1820 is a dominant species (Sinka et al, 2010) and it constitutes one of the main Colombian vectors (Gutiérrez et al, 2008; Montoya-Lerma et al, 2011; Quiñones et al, 1987) typically found in low coastal lands under 400 m (Fleming, 1986), but it has also been recorded at high altitudes (995–1941 m) (González and Martínez, 2006; Martínez-Palacios and Pletsch, 1963). It is a generalist species (Fuller et al, 2012); immature stages develop in a wide variety of breeding sites and can tolerate a wide range of water conditions such as salinity, turbidity and pollution (Faran, 1980; Henderson, 1948). Adult females exhibit plasticity in blood-feeding behavior, biting humans or animals, indoors or outdoors (Olano et al, 1997), and can fly up to 32 km (Breeland, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha planteado la hipótesis de que el cambio global en el clima generará condiciones desfavorables para An. albimanus en ciertas regiones de Mesoamérica, incluida La Guajira, lo cual podría ocasionar un desplazamiento de la especie a zonas con condiciones más favorables para su desarrollo, aumentando así su rango de distribución geográfica (46). Sin embargo, esta transición hacia un incremento en la temperatura ambiental puede contribuir a aumentar el riesgo de transmisión de la enfermedad debido a que los ciclos gonotróficos se hacen más cortos, y ello se traduce en un mayor número de picaduras (47).…”
Section: Discussionunclassified